Ruling with ideology: Politicians’ beliefs and privatizations - Ma, Linxiang (Journal of Corporate Finance, 2026)
I examine how political ideology shapes China’s privatization wave around 2000. Using a novel ideology measure constructed based on belief formation mechanisms, I show that provincial governors with above-median communist beliefs privatize 2.8% fewer state-owned enterprises (SOEs) each year than their below-median-belief colleagues. Firms privatized under such governors also achieve fewer efficiency gains after the sale. Mechanism analysis finds evidence that this performance gap arises from ideologically driven choices: pro-communist governors are more likely to privatize weaker or less important firms, adopt transaction structures associated with inferior outcomes, and manage subsidies in ways that exacerbate post-privatization challenges. Moreover, ideology moderates how governors learn from experience and respond to signals, shaping their adaptation in managing privatization. Jointly, these results demonstrate that political leaders’ beliefs can substantially influence the trajectory and outcome of major economic reforms. It also highlights the importance of ideology in driving politicians’ decisions under authoritarian regimes.